Gaya Kepemimpinan Kepala Kua dalam Peningkatan Motivasi dan Kinerja Pegawai di KUA Kecamatan Padang Utara - Putri, Ramayani; Alzyirah, Syahfitri; Agustina, Tricilia (Jurnal Komunikasi dan Ilmu Sosial, 2023)
This research aims to determine the leadership style of the head of the North Padang District religious affairs office in increasing employee motivation and performance and to determine the obstacles to increasing employee motivation and performance. The leadership style applied by the Head of the Office of Religious Affairs (KUA) is not only limited to leading but also to motivation and has a big influence on employee performance. In leading the Office of Religious Affairs (KUA), of course, the leader has a big responsibility, especially in terms of providing motivation and direction to employees. In implementing his leadership style, of course, a leader must be responsible for all decisions taken, and also responsible for employee performance. In implementing his leadership style, the head of the North Padang District KUA must of course consider all his actions, because this greatly influences employee attitudes or relationships between employees and employee relationships with superiors. This research uses qualitative research. The results of the research show that the leadership style in motivating employee performance at KUA North Padang District has brought many changes to its employees such as increasing employee performance, thus indirectly the decisions and methods of motivation carried out by the Head of KUA North Padang District have had a very good impact on KUA the. However, there are various obstacles in implementing this decision, one of which is the different characteristics of employees and also some employees who find it difficult to adapt to the rules or policies that have been made by the Head of KUA.